2018
DOI: 10.1186/s40798-018-0148-x
|View full text |Cite
|
Sign up to set email alerts
|

Exercise in Pregnancy and Children’s Cardiometabolic Risk Factors: a Systematic Review and Meta-Analysis

Abstract: BackgroundMaternal metabolic health during the prenatal period is an established determinant of cardiometabolic disease risk. Many studies have focused on poor offspring outcomes after exposure to poor maternal health, while few have systematically appraised the evidence surrounding the role of maternal exercise in decreasing this risk.The aim of this study is to characterize and quantify the specific impact of prenatal exercise on children’s cardiometabolic health markers, at birth and in childhood.MethodsA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 120 publications
0
15
0
Order By: Relevance
“…Fifty-six were excluded as they did not report meta-analysis of health-related outcomes, leaving 65 which met the inclusion criteria and were included in this review ( Table S5 ). There were 63 [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , ...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fifty-six were excluded as they did not report meta-analysis of health-related outcomes, leaving 65 which met the inclusion criteria and were included in this review ( Table S5 ). There were 63 [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Out of the 63 included reviews that reported interventions with different diet- and/or physical-activity-related components, 19 reported effectiveness data for diet-only interventions [ 30 , 35 , 39 , 40 , 42 , 44 , 45 , 51 , 52 , 55 , 62 , 63 , 65 , 67 , 69 , 82 , 85 , 89 , 90 ], 37 reported data for physical-activity-only interventions [ 33 , 36 , 38 , 39 , 42 , 46 , 47 , 48 , 49 , 51 , 52 , 53 , 54 , 55 , 59 , 62 , 66 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 78 , 80 , 81 , 82 , 83 , 84 ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Obesity and metabolic syndrome (MetS) are two of the most common chronic diseases among children. Recent evidence suggests these conditions have their roots in utero as maternal obesity, dyslipidaemia, and hyperglycaemia are associated with child cardiometabolic health and developing insulin resistance and obesity later in life [85,86]. Although studies considered in this review indicate that higher adherence to the MD during pregnancy is a potential protective factor against abdominal obesity [73,74] and positively influences lipoprotein and homocysteine concentration [76], and insulin resistance in new-borns [70], the use of different endpoints to evaluate outcomes reduces the level of evidence.…”
Section: Discussionmentioning
confidence: 99%